Diseases of tropical Acacias: proceedings of an International Workshop held at Subanjeriji (Southern Sumatra), 28 April - 3 May 1996 - Old, K.M.; Lee Su See; Sharma, J.K. (Center for International Forestry Research, 1997)
Acacias are of considerable social and industrial importance for tropical reforestation and it is expected that about 2 million hectares will be established in Southeast Asia by the year 2000. The acacia species currently of most interest for plantation forestry in the tropics are indigenous to northern Australia, Papua New Guinea and Irian Jaya. Recent reports from Malaysia, Indonesia, Thailand and northern Australia suggest that the future productivity of acacia plantations may be affected by fungal pathogens including leaf spots, shoot blights, stem cankers, heart rot, root rots and gall rusts. During 1995-96 a series of disease surveys was undertaken by forest pathologists in native stands, trials, and operational and social forestry plantings of tropical acacias in Australia, India, Indonesia, Malaysia and Thailand to assess the potential of fungal pathogens as limiting factors to tree growth and productivity and to assess the relative importance of individual fungal pathogens. Tree species included in the surveys were Acacia mangium and A. auriculiformis, on the basis of their current importance as plantation species. A. crassicarpa and A. aulacocarpa were also surveyed as, although they have been planted on a limited scale so far, they are included in provenance and species trials in many locations throughout the region. Scientists who had participated in the project met with research managers of five major Indonesian plantation pulp and paper companies and government business enterprises from 28 April - 3 May 1996 at the base camp of PT Musi Hutan Persada Subanjeriji in southern Sumatra, to present the results of their surveys. This publication is a status report on the diseases of acacias in the several countries based on information presented at the workshop. It provides a benchmark of the current knowledge of the pathology of the four most important Acacia species currently being grown in plantations in tropical areas of Southeast Asia, the Indian subcontinent and northern Australia.